DESENVOLVIMENTO, CARACTERIZAÇÃO E AVALIAÇÃO DE MICROPARTÍCULAS POLIMÉRICAS CONTENDO MANIDIPINA - Barboza, Fernanda Malaquias (2013)
Manidipine is a third-generation calcium channel blocking effective in the treatment of hypertension, which its use has been related to further metabolic effects of potential clinical interest. However, its high lipophilicity results in undesirable physicochemical and biopharmaceutical properties. Thus, a pharmaceutical improvement is necessary to achieve a remarkable advance in its absorption and bioavailability. In that sense, the aim of this paper was to microencapsulate the manidipine in order to avoid its spontaneous compartmentalization in adipocytes and make its intestinal transit longer, with appropriate release rates and duration to generate the desired antihypertensive effect. Poly(ε-caprolactone) (PCL) and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) microparticles containing manidipine were successfully prepared by simple emulsion/solvent evaporation method. Considering the lack of validated methods for drug quantification in these microparticles, an analytical method by high efficiency liquid chromatography with spectrometric detection in the ultraviolet region was previously developed and validated. This method proved to be selective, linear (r = 0.9992), precise (RSD < 2.08 %) and accurate (recovery capacity between 95.02 and 100.41%) in the range from 10 to 50 μg.mL-1. The chromatography was robust when underwent slight variations in the mobile phase composition and column temperature. All four formulations showed loading efficiency rates greater than 80% and average particle sizes less than 8 μm. Microparticulate systems showed a spherical shape with smooth and porous surface for PCL and PHBV formulations, respectively. According to Fourier-transformed infrared analysis, initial components were not chemically modified during microencapsulation process, whereas X-ray diffraction patterns and differential scanning calorimetry analysis demonstrated that this process led to drug amorphization. In vitro dissolution profile showed that all microparticles prepared were able to sustain manidipine release, especially which one prepared from PCL, that contained 5% of the drug loaded (PCL-M5). Animal studies demonstrated that PCL-M5 formulation was able to hold the mean arterial pressure variation after phenylephrine administration up to 24 hours. These data demonstrate the sustained antihypertensive effect of the proposed microparticles. Results provided an experimental basis for using PCL-M5 formulation as an oral manidipine carrier.